MOLECULAR SEQUANCING AND PHYLOGENIC ANALYSIS TO VIRULENCE nmuc-1 GENE IN VISCERAL LARVAE MIGRANCE - Hade, B. F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Toxocariasis is a zoonotic parasitic disease caused by Toxocara canis infected egg. Larval stage of this parasite has ability to migrate through intestinal wall and invade all body organs causing a visceral larvae migrant (VLM) syndrome. Diagnosis of VLM is problematic; there were no accurate laboratory test that reveals the presence of larvae infection in paratenic hosts (human, ruminants or poultry). The eggs were isolated from adult T. canis uteri and cultured in 0.2M H2S04 solution for embryonation, mice were experimentally infected with emberyonated eggs. Many hisopathological changes detected in heart and kidney tissues of infected mice but it could not detected encysted larvae compared with molecular detection which confirmed infection within first three day post infection in tissue with accurate diagnosis for the first time in Iraq depend in detected virulence nmuc-1 gene. Phylogenic tree analyses mounted a low genetic variation (0.2) among Iraqi isolate and all other comparison isolates. In conclusion our result indicated that molecular method could diagnosis T. canis larvae infection in any meat or meat products of local or imported from inside or outside Iraq country and used as an accurate microbiological laboratory test used routinely in government laboratories.